The Evidence of Epicurean (Greek Text) and Its Practical Scope; [la Evidencia de la (Greek Text) Epicúrea y Su Alcance Práctico] - Aoiz-Monreal, F (Ediciones Universidad de Salamanca, 2024)
This paper discusses the Epicurean preconception and the issues related to its acquisition and function (both in theoretical and practical domains). The authors argue that in the Epicurean contractual model justice is regarded as a modality of the useful and that the preconception of the just is a canon that validates the laws in the political communities. They also examine the link between language and justice in Epicureanism, focusing first on the role of language in the Epicurean genealogy of justice and, second, on the connections between language learning and the prolepsis of the just in constituted political communities. In this vein, they hold that language learning is a relevant ingredient of experience for understanding the empirical genesis of the Epicurean preconception. © 2024 Ediciones Universidad de Salamanca. All rights reserved.